Effectiveness of Mutual Legal Assistance Treaty in Investigating Indonesian Kidney Sale Crimes in Cambodia - Saragih, Jogi Talar; Aditama, Yuda Lambang; Siahaan, Herbin Marulak (Magister Hukum Universitas Semarang, 2024)
This paper addresses the pressing issue of human trafficking in the ASEAN region, focusing on the role of the Mutual Legal Assistance Treaty (MLA) as a legal strategy for regional collaboration. Human trafficking is not only a grave violation of human rights but also a complex transnational crime that requires coordinated international efforts. This study investigates the existing legal framework, policies, and institutional mechanisms in ASEAN to combat human trafficking. The study identified significant challenges faced by MLA, including limitations in the legal framework and coordination issues among member states. The findings suggest that strengthening MLA as an integrated legal approach that encompasses prevention, prosecution, protection, and cross-border cooperation is hampered because corruption and complicity of officials in trafficking crimes at various levels of government continue to be significant problems, which impede law enforcement and perpetuate impunity to effectively combat trafficking. The study uses comparative legal analysis to highlight the importance of strong regional collaboration, emphasising the need for improved information sharing and coordination to enhance legal and institutional responses. The paper concludes that a stronger MLA framework is essential to address the complexities of trafficking and provide better support for victims.